Technical and economic effectiveness of weeding spraying method in oil palm plantation / Wan Mohamad Firdaus Wan Khalid - Wan Khalid, Wan Mohamad Firdaus (Faculty of Plantation and Agrotechnology, 2017)
Now days, weeding is a common problem at oil palm plantation and giving crisis to the production of oil palm when not controlled. Usually, the common weeding spraying method will be divide into two methods such as circle spraying and selective spraying. In this study, the comparison of the technical efficiency and economic spraying method in oil palm plantation will be done to find the best process from two different companies. This study was conducted in Felcra Berhad Kawasan Sg Sepuluh and Kulim (M) Berhad Ladang Rengam at Kluang Johor. The data collection method for this study was by using secondary data type and interview consist of costing operation, map of field, type of herbicide used and no of workers data. The data will be analyses by using descriptive analysis, t-test and partial budget by using the software SPSS and Microsoft Excel. In the end of study, the results shows the cost implication and different spraying method from two different companies. From the result, it was shown all the plantation companies need to choose the best spraying method based on their capacity to increase the profit of the organization.